Reincidência criminal e sua atuação como circunstância agravante - Chiquezi, Adler (2009)
This work analyses criminal recidivism and its role in aggravating penalty, in order to study the way Brazilian Legislation deals with it according to the evolution of the Penal Law. With this purpose the recidivism has been collated rationally from a general to private matter. It looks into the recidivism, its classification and related subjects, and evaluate its evolution in the Brazilian Penal Law it also analyses theories that justifies its application, furthermore it lists its penal and procedural effects coming from the recognition of recidivism. The main goal of this paper is to question the recidivism in the current Brazilian Law (Mainly through the Brazilian Federal Constitution/ 1988) due to the failure of the prison penalty to reintegrate the criminal in the society. After verifying how other countries use the recidivism, we suggest changes for it in Brazil according to compared law and the evolution in penal law, making sure the penal law will truly be applied .The crisis of the prison system is highlighted, giving emphasis to the overpopulation of our prisons, no existence of reintegration programs and lack of support to the ex convicts, all these factors leads to high rates of recidivism